Effects of Annona muricata Extract on Trypsin, Cathepsin B and Collagenase Activities and Textural Changes in Chilled Macrobrachium rosenbergii - Amalina Ibrahim; Kamariah Bakar; Jamilah Bakar; Nilesh Prakash Nirmal; Mhd Ikhwanuddin; Nurul Ulfah Karim (Foods, 2023)
Texture is an important sensory attribute for overall quality and consumer acceptance of prawns. However, texture is affected during cold storage due to the proteolytic activity of endogenous proteases, resulting in poor quality and a short shelf life. The objective of this study is to determine the inhibitory effects of Annona muricata leaves extract (AMLE) (0, 3, 10 and 20%) on the trypsin, cathepsin B and collagenase activities extracted from the cephalothorax of Macrobrachium rosenbergii. In addition, the textural changes in M. rosenbergii during 20 days of cold storage (4 °C) were also determined. M. rosenbergii were soaked in four different treatments: 0, 3, 10 and 20% AMLE and 1.25% sodium metabisulphate for 10 min at 4 °C. Protease activity was significantly (p < 0.05) reduced at 10 and 20% AMLE. Similarly, cathepsin B showed a significant (p < 0.05) low after treatment at 20% AMLE. The maximum inhibitory activity of trypsin was achieved at 20% AMLE and the standard inhibitor (Tosyl-L-lysyl-chloromethane hydrochloride (TLCK)) compared to the control. Whereas, the lowest collagenase activity was obtained at 20% AMLE compared to the control. These inhibitory effects further maintain the firmness of M. rosenbergii coated with 20% AMLE up to the eighth day of storage when compared to the control. Meanwhile, the highest penetration work was found in the M. rosenbergii coated with 20% AMLE at the twentieth day of storage. In conclusion, treatment at 20% AMLE could be used as a natural preservative to inhibit protease, trypsin and collagenase activity of M. rosenbergii and thus can maintain firmness for up to 8 days of storage.